1999
DOI: 10.1098/rspb.1999.0902
|View full text |Cite
|
Sign up to set email alerts
|

Nest predation and the evolution of nestling begging calls

Abstract: Begging by nestling birds can be conspicuous and loud. Such displays are thought to function in signalling nestling condition and securing parental care, but they also may inadvertently attract the attention of predators. We compared the structure of nestling begging calls to the risk of predation among 24 species of birds breeding in a forest community in central Arizona. After controlling for body size and phylogeny, we found that species subject to greater nest predation had calls with higher frequency (pit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
108
1
2

Year Published

2000
2000
2011
2011

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 163 publications
(112 citation statements)
references
References 27 publications
1
108
1
2
Order By: Relevance
“…Most studies on begging behaviour have taken place in passeriform birds, and based on the results it may well be that chicks convey information on their nutritional needs (Iacovides and Evans 1998;Kilner and Johnstone 1997;Price and Ydenberg 1995;Redondo and Castro 1992). However, these results were partly clouded by the fact that begging behaviour is also influenced by nestling competition (Neuenschwander et al 2003;Price 1996), previous feeding experiences (Kedar et al 2000;Rodriguez-Girones et al 2002) and predation pressure (Briskie et al 1999). …”
Section: Introductionmentioning
confidence: 69%
“…Most studies on begging behaviour have taken place in passeriform birds, and based on the results it may well be that chicks convey information on their nutritional needs (Iacovides and Evans 1998;Kilner and Johnstone 1997;Price and Ydenberg 1995;Redondo and Castro 1992). However, these results were partly clouded by the fact that begging behaviour is also influenced by nestling competition (Neuenschwander et al 2003;Price 1996), previous feeding experiences (Kedar et al 2000;Rodriguez-Girones et al 2002) and predation pressure (Briskie et al 1999). …”
Section: Introductionmentioning
confidence: 69%
“…Instead, as we show here, it can actually re£ect a strong proximate e¡ect of parental activity o¡setting antagonistic nest site e¡ects. Ultimately, nest predation can exert strong selection on a wide variety of phenotypic traits (Skutch 1949;Slagsvold 1982Slagsvold , 1984Martin 1992aMartin , 1995Martin , 1998Redondo & Castro 1992;Bosque & Bosque 1995;Briskie et al 1999;Conway & Martin 2000;Ghalambor & Martin 2000;Martin et al 2000) making identi¢cation of the ecological factors that in£uence the risk of nest predation necessary. Previous work has suggested that nest site selection within species as well as di¡erences in nest types between species are important determinants of variation in nest predation risk (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…In experiments with loudspeakers in dummy nests, they demonstrated that the calls of tree-nesters produced higher predation rates (than those of ground-nesters) when played on the ground, but that the calls of ground nesters did not increase predation risk (compared with tree-nesters) when played in dummy nests in the trees. Briskie et al (1999) studied a 24-species community of breeding passerines, measuring egg loss from predation and recording begging calls. Controlling for phylogeny, they found a relationship where species with higher predation rate had calls of higher frequency and lower amplitude.…”
Section: Soundmentioning
confidence: 99%